Cell Activation-Induced Phosphoinositide 3-Kinase Alpha/Beta Dimerization Regulates PTEN Activity - Pérez-García, Vicente (American Society for Microbiology, 2014)
The phosphoinositide 3-kinase (PI3K)/PTEN (phosphatase and tensin homolog) pathway is one of the central routes that enhances cell survival, division, and migration, and it is frequently deregulated in cancer. PI3K catalyzes formation of phosphatidylinositol 3,4,5-triphosphate [PI(3,4,5)P(3)] after cell activation; PTEN subsequently reduces these lipids to basal levels. Activation of the ubiquitous p110α isoform precedes that of p110β at several points during the cell cycle. We studied the potential connections between p110α and p110β activation, and we show that cell stimulation promotes p110α and p110β association, demonstrating oligomerization of PI3K catalytic subunits within cells. Cell stimulation also promoted PTEN incorporation into this complex, which was necessary for PTEN activation. Our results show that PI3Ks dimerize in vivo and that PI3K and PTEN activities modulate each other in a complex that controls cell PI(3,4,5)P(3) levels.